Local structure of Yb3+ ions and X-ray induced defect in Yb-doped silica glass. (19th November 2018) - Okazaki, T.; Sekiya, E. H.; Saito, K.
Abstract: The local structure of Yb 3+ ions in Yb-doped silica glass was investigated by extended X-ray absorption fine structure, the Rayleigh scattering and optical absorption measurements. It was found that the Yb coordination number increases from 3 to 4.5 with increasing Yb concentration. Simultaneously, the absorption cross-section of Yb 3+ ion decreases and the Rayleigh scattering coefficient increases. These results suggest that local structure observed in Yb2 O3 or Yb2 Si2 O7 crystals appears in high-Yb samples. Furthermore, photodarkening by X-ray irradiation was measured, and the correlation to the local structure change was clarified.